2013
DOI: 10.1371/journal.pone.0077744
|View full text |Cite
|
Sign up to set email alerts
|

A Field Evaluation of an External and Neutrally Buoyant Acoustic Transmitter for Juvenile Salmon: Implications for Estimating Hydroturbine Passage Survival

Abstract: Turbine-passed fish are exposed to rapid decreases in pressure which can cause barotrauma. The presence of an implanted telemetry tag increases the likelihood of injury or death from exposure to pressure changes, thus potentially biasing studies evaluating survival of turbine-passed fish. Therefore, a neutrally buoyant externally attached tag was developed to eliminate this bias in turbine passage studies. This new tag was designed not to add excess mass in water or take up space in the coelom, having an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Thus, since the life of small electronic tags is usually low (but see [39]), external tagging can be preferred due to lower acute health effects compared to surgical implantation, where a longer recovery period may be evident. In a field study on Chinook salmon smolts, Brown et al [40] observed 10 % tag loss 9-17 days after tagging, as well as a high proportion of tags that were loose or displaced. In another laboratory study on Chinook smolts, only 5 % of the fish lost the external tags within 2 weeks [41], but tearing and loosening of the sutures holding the tags were also observed.…”
Section: Cebidichthys Violaceusmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, since the life of small electronic tags is usually low (but see [39]), external tagging can be preferred due to lower acute health effects compared to surgical implantation, where a longer recovery period may be evident. In a field study on Chinook salmon smolts, Brown et al [40] observed 10 % tag loss 9-17 days after tagging, as well as a high proportion of tags that were loose or displaced. In another laboratory study on Chinook smolts, only 5 % of the fish lost the external tags within 2 weeks [41], but tearing and loosening of the sutures holding the tags were also observed.…”
Section: Cebidichthys Violaceusmentioning
confidence: 99%
“…Brown et al [81] compared survival of externally tagged hatchery-reared Chinook salmon juveniles during simulated turbine passage (laboratory) and found no difference in mortality between tagged and control fish. A further (field) comparison between surgically implanted (PIT-tags) and externally tagged hatchery-reared Chinook smolts during passage of hydropower stations and along river reaches showed that external tags were suitable for short-term migration studies, but not for longer periods than 10 days due to tag loss and mortality [40]. In masu salmon (Oncorhynchus masou) juveniles, kept in an outdoor tank, 83 % of externally tagged and 42 % of surgically implanted fish died within 68 days [68].…”
Section: Survivalmentioning
confidence: 99%
“…Carlson et al (2012) demonstrated that for juvenile Chinook Salmon exposed to rapid decompression associated with simulated turbine passage, the probability of injury and mortality increased as tag burden increased. To overcome this, we recommend using the smallest tag possible to minimize tag burden or a neutrally buoyant, externally attached tag (tag burden of 0%; Deng et al 2012;Janak et al 2012;Brown et al 2012dBrown et al , 2013b, when examining survival of fish exposed to rapid decompression associated with infrastructure passage. In addition, having a telemetry transmitter inside the body cavity may limit the amount that a swim bladder can expand before it ruptures or causes compression-related injuries.…”
Section: Field Validation Of Modeled Mortality Relationshipsmentioning
confidence: 99%
“…Therefore, field estimates of mortality that are based upon tagged fish have the potential to overestimate the severity of barotrauma injury. To overcome this, we recommend using the smallest tag possible to minimize tag burden or a neutrally buoyant, externally attached tag (tag burden of 0%; Deng et al 2012;Janak et al 2012;Brown et al 2012dBrown et al , 2013b, when examining survival of fish exposed to rapid decompression associated with infrastructure passage.…”
Section: Field Validation Of Modeled Mortality Relationshipsmentioning
confidence: 99%
“…gadoids, sparids) cannot. Physoclistous fish slowly regulate air exchange via blood diffusion through a network of small vessels located on the swim bladder membrane, making them more susceptible to barotrauma when passing through hydroelectric turbines (EPRI 2011a;Brown et al 2013;Brown et al 2014).…”
Section: Hydropower Developmentmentioning
confidence: 99%